Democratic Consumption (In Factis Pax: Journal of Peace Education and Social Justice, 2021)
This think piece explores the idea of democratic consumption. After explaining its etymological roots, 12 principles of democracy are described. A narrative of the review of literature (organized by century 19th, 20th and 21st) is followed with an analysis of common threads and emergent patterns. Five ideas were associated with democratic consumption with nominal agreement on how and in what direction: common good, economic freedom and capitalism, welfare state, ethical consumption, and diverse consumer interest. Although the focus of democratic consumption has changed over time, it is consistently linked with several principles (e.g., economic freedom, equality, freedom and rights, and the rule of law) and it eschews others (e.g., an independent judiciary). Consumer, philosophy, political, social welfare, economic, and peace theorists are encouraged to empirically explore what constitutes democratic consumption defined tentatively as behaviour having to do with consumption reflective of and influenced by democratic principles for a myriad of reasons.
Keywords: democratic consumption; emocratic principles; onsumer behaviour; common good; economic freedom